Electroactive Co(iii) salen metal complexes and the electrophoretic deposition of their porous organic polymers onto glassy carbon. Issue 43 (3rd July 2018) - Solomon, Marcello B.; Rawal, Aditya; Hook, James M.; Cohen, Seth M.; Kubiak, Clifford P.; Jolliffe, Katrina A.; D'Alessandro, Deanna M.
Abstract : We report the synthesis, characterisation and electrochemistry of Co(iii ) salen metal complexes and their porous organic polymers for CO2 electroreduction. Abstract : This paper reports the CO2 electroreduction properties of three bis-bromo Co(iii ) salen metal complexes and their Porous Organic Polymers (POPs) as a platform for using the salen core as a multi-electron reducing agent. Although Co(iii ) salen metal complexes have been studied extensively for their chemical catalysis with CO2, their electrochemical behaviour, particularly their reduction, in the presence of CO2 is much less explored. The discrete Co(iii ) complexes enabled the reduction of CO2 to CO in faradaic efficiencies of up to 20%. The reductive electrochemical processes of Co(iii ) salen complexes are relatively unknown; therefore, the mechanism of reduction for the complexes was investigated using IR and UV-Vis-NIR spectroelectrochemical (SEC) techniques. The discrete bis-bromo salen complexes were incorporated into POPs with tris-( p -ethynyl)-triphenylamine as a co-ligand and were characterised using solid state NMR, IR, UV-Vis-NIR and Field Emission Scanning Electron Microscopy (FE-SEM). The POP materials were electrophoretically deposited onto glassy carbon under milder conditions than those previously reported in the literature. Direct attachment of the POP materials to glassy carbon enabled improved solid state electrochemical analysis of the samples. The POP materials were also analysed via SEC techniques, where a Co(ii /i ) process could be observed, but further reductions associated with the imine reduction compromised the stability of the POPs.